A method to culture chicken enterocytes and their characterization. (15th June 2018) - Rath, Narayan C; Liyanage, Rohana; Gupta, Anamika; Packialakshmi, Balamurugan; Lay, Jackson O
ABSTRACT: Enterocytes function as both absorptive and protective components of intestine that come in close contact with a variety of enteric factors, such as dietary, microbial, and parasites, that have potential to affect the organismal health. Understanding how enterocytes interact with this complex array of factors may help improve gut health particularly in the context of poultry production where it is also linked to food safety issues. The enterocyte in vitro culture can help screen different factors and their interactions with microbiome, and potentially be utilized in the development of interventions strategies for pathogens such as antibiotic alternatives. We developed a method to culture primary chicken enterocytes and conducted their characterization using cytochemical and proteomic methods, and investigated their potential to respond to different chemical stimuli. Using selected micronutrients, microbial toxins, and metabolic modulators, we assessed their effects on the viability and morphological changes in enterocytes. We found that whereas some nutritional factors (calcitriol, retinoic acid) produced different morphological changes, toxins such as aflatoxin B1 and deoxynivalenol produced enterocyte degeneration and death, and the bacterial lipopolysaccharide had very little effect compared on the basis of their mass. Both cyclic AMP and phorbol myristate acetate exhibited some cachectic effects on enterocytes with the later showing more severe changes. Thyroxin induced distinct morphological changes making the cells more cuboidal and Na-butyrate produced no significant change in morphology. The cytochemical and proteomic characterization suggest that these enterocytes largely belong to epithelial cell categories which may be amenable to analysis of biochemical paths and mechanisms of action of different factors that affect these cells. Based on these results we conclude that chicken enterocyte culture can be a useful in vitro model to study intestinal physiology.